2022
DOI: 10.1002/cpe.7277
|View full text |Cite
|
Sign up to set email alerts
|

Application of rough set theory and machine learning algorithms in predicting accident outcomes in the Indian petroleum industry

Abstract: Summary Recent advancements in machine learning techniques are helping researchers to develop predictive models that assist decision‐makers to get a quick, unbiased overview of the processes. But studies using machine learning approaches in analyzing and classifying the injury narratives of the petroleum industries are still in their early stages due to data unavailability and lack of trust in these models. Comparatively, other industries such as construction, manufacturing, aviation and so forth are using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…In recent years, there has been a growing focus on research that looks at the possibilities of machine learning for incident and occupational risk prevention at the workplace. One example of such a study is the work [1,2,13], which studied the use of machine learning to predict incidents in oil and gas fields. The study showed that the use of machine learning can significantly improve incident prediction and reduce risks for employees and the organization.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been a growing focus on research that looks at the possibilities of machine learning for incident and occupational risk prevention at the workplace. One example of such a study is the work [1,2,13], which studied the use of machine learning to predict incidents in oil and gas fields. The study showed that the use of machine learning can significantly improve incident prediction and reduce risks for employees and the organization.…”
Section: Resultsmentioning
confidence: 99%